Determination of radical scavenging activity and vitamin A, C and E in organically grown red pitaya (Hylocereus sp.) - Rohin, Mohd Adzim Khalili; Abd. Hadi, Norhayati; Mohd Yusof, Rokiah; Rahmat, Asmah; Mansor, Siti Muskinah; Ali, Abdul Manaf (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
This study was conducted to determine radical scavenging activity and vitamin antioxidant composition in red pitaya from organic plantation. For antioxidant vitamins analysis, a reverse-phase high performance liquid chromatography was used and radical scavenging activity of methanolic and water extract were determined using 1,1-diphenyl-2-pircrylhydrazyl assay. Results for radical scavenging activity, red pitaya methanolic extract achieved the highest percentage 70.13% compared with water extract (47.13%). Antioxidant vitamins composition in red pitaya showed that the concentration of vitamin A is 120.13 ± 0.69 μg/100 g freeze-dried sample, vitamin C is 540.27 ± 0.59 μg/100 g fresh samples and vitamin E is 105.67 ± 0.56 μg/100 g freeze-dried samples. This shows that red pitaya may become an alternative and potential source of natural antioxidant.